(untitled) (Journal of Enam Medical College, 2017)
Guillain-Barré syndrome (GBS) is an acquired acute autoimmune polyradiculoneuropathy. Progressive motor weakness and areflexia are essential for diagnosis. But in some cases hyperreflexia can be seen. Diagnosis of GBS was made based on history and clinical findings and was supported by cerebrospinal fluid (CSF) studies and nerve conduction study (NCS). We hereby report a case of a 42-year-old male presenting with acute onset flaccid quadriparesis. There was frank hyperreflexia in all four limbs. Although reflex preservation and hyperreflexia can be noted in axonal variant of GBS in Chinese, Japanese, and European populations, it is uncommon in India. J Enam Med Col 2017; 7(2): 111-112